Analisis Pengaruh Tekanan dan Suhu Sirkulasi Pendingin pada Kompressor Oksigen Bertekanan Tinggi 2000 PSI/150 Bar - Nurhakim; Komarudin (Quantum Teknika : Jurnal Teknik Mesin Terapan, 2025)
High‑pressure oxygen compressors are vital assets in hospitals to ensure continuous medical oxygen supply. The gas compression process generates considerable heat, which, if not properly controlled, can reduce efficiency and damage components. This study analyzes the effect of increasing pressure on temperature across different compression stages and evaluates the cooling circulation system performance of a 2000 PSI/150 Bar oxygen compressor at Redabolo Regional Hospital, Southwest Sumba. A quantitative experimental method was applied, recording temperature and pressure data at four compression stages and two cooling circulation points (bottom and top) under pressures of 0, 1000, and 2000 PSI. The data were processed to determine temperature changes (ΔT), actual heat transfer, and cooling and heat transfer efficiencies. Thermodynamic verification of adiabatic and isothermal processes was conducted using the ideal gas law.Results indicated that temperatures rose with increasing pressure, with the most significant rise occurring in Stages 3 and 4, reaching 89–90°C at 2000 PSI. The cooling circulation system proved highly effective, achieving approximately 83.05% cooling efficiency and 98.16% heat transfer efficiency. Verification confirmed that compression was neither purely adiabatic (due to active cooling) nor isothermal (due to rising temperature). Operating temperatures near the maximum limit at high pressure highlighted the need for heat management and predictive maintenance. The absence of post‑operation cooling in the second experiment emphasized its importance for component integrity. In conclusion, the compressor operated effectively with a reliable cooling system, though high temperatures in the final stages remain a concern. Recommendations include enhanced temperature monitoring, evaluation of cooling capacity, and strict post‑operation cooling procedures to minimize risks and optimize long‑term performance.